The impact of trade, financial development and government integrity on energy efficiency: An analysis from G7-Countries. (15th September 2022) - Shah, Wasi Ul Hassan; Hao, Gang; Yan, Hong; Yasmeen, Rizwana; Padda, Ihtsham Ul Haq; Ullah, Assad
Abstract: G7-countries have pivotal collaborations in several domains, including energy efficiency to realize energy security and subside greenhouse gas emissions. In this respect, research on these countries' energy efficiency merits attention. Concurrently, trade is a significant driver for promoting energy-efficient technologies across seven countries. Thus, this study examines the relationship between energy efficiency, trade, financial development, and government integrity of G7 economies for the period spanning 1996 to 2015. The Data Envelopment Analysis is applied to estimate the energy efficiency of these countries. The study employed the Driscoll & Kraay method and found that trade is an effective channel to increase energy efficiency. However, the study established two critical points. Firstly, research and development (innovations) increase trade but not improve energy efficiency. Secondly, governance plays a positive role in boosting trade but is less focused on improving energy efficiency. Moreover, financial development enhances energy efficiency. The study recommends establishing a clear linkage between government integrity and energy efficiency; unless a clean environment is not the government's top priority, the objective of a cleaner environment cannot be achieved. Trade, financial development, and R&D in energy efficiency projects could play a cardinal role. Highlights: DEA with undesirable output is used to estimate the energy efficiency of G7. . Role of government integrity in determining energy efficiency has been explored. Trade and its parts, exports & imports are important energy efficiency factors. Two important determinants, research & development and financial support are used. Aim of cleaner environment can be achieved by prioritizing only clean environment.